Interleukin-10 involvement in exposure to low dose of benzene. (April 2015) - Spatari, Giovanna; Saitta, Salvatore; Giorgianni, Concetto; Cristani, Maria Teresa; Quattrocchi, Paolina; Abbate, Adriana; Carrieri, Mariella; Ferraro, Giorgia; Saija, Antonella; Gangemi, Sebastiano
Objective: To establish if serum levels of interleukin-10 (IL-10) in subjects exposed to benzene are connected with age, working years, and employment age. Methods: We evaluated serum levels of IL-10 in 51 employees working in oil refinery (group A) and in 16 office workers who resided in the same area (group B). Results: There was no statistically significant difference between serum concentrations of IL-10 in groups A and B. There was a statistically significant dependent relationship in group A between age, working years, and serum concentration of IL-10. There was a statistically significant and positive dependent relationship in group A between serum concentration of IL-10 and employment age. Conclusions: The role played by IL-10 in benzene immune suppression may be relevant and attention should be directed toward assessment of age, working years, and employment age in benzene-exposed populations.